Los indicadores de evaluación y los niveles de calidad de la composición escrita - Albarrán Santiago, Manuel (Didáctica. Lengua y Literatura, 2009)
Evaluating composition is a regulating process of writing, the main goal of which is to detect any difficulties and/or progress in the process of learning it. In order to do the evaluation, it is advisable to base on indicators originated from the cognitive process related to writing, and from the resulting product. These indicators show specifically the quality level of written composition produced by high-school students; for the purpose of testing its functionality, efficiency, and effectiveness. This proposal resulted from the analysis of various readings and research, and it aims at suggesting what, how, when, and why evaluating the production of a piece of writing. These results may be used for guiding teaching and learning process.En francés:L'évaluation de la composition est un processus de régulation de l'écriture, dont le principal objectif est de détecter les difficultés et / ou les progrès dans le processus d'apprentissage. Dans le but de faire l'évaluation, il est conseillé se baser sur les indicateurs proviennent des processus cognitifs liés à l'écriture et du produit obtenu. Ces indicateurs montrent précisément le niveau de qualité de la composition écrite produite par des lycéens, dans le but de tester la fonctionnalité, l'efficacité et l'efficience. Cette proposition résulte de l'analyse de diverses lectures et de la recherche, et il s'agit de proponer quoi, comment, quand et pourquoi l'évaluation de la production d'un texte écrit. Ces résultats peuvent être utilisés pour guider les processus d'enseignement et apprentissage.
Keywords: Evaluation of writing; Indicators; Quality; Évaluation de l'écriture; Indicateurs; Qualité